The Influence of Image Media on Early Childhood Learning Motivation - Wahyuni, Gusti; Pebriani, Sri Ismi; Lestari, Suci Ayu; Lesbatta, Delkia; Herman, Herman (Newinera Publisher, 2025)
This study investigates the impact of image-based media on early childhood learning motivation at Al-Furqon Islamic Kindergarten in Makassar, Indonesia. From the perspectives of intrinsic motivation and multimedia learning the study implements both quantitative data with a quasi-experimental one-group pretest–posttest design and qualitative classroom observation methods. The intervention involved Group B children viewing visual materials showing familiar cultural farm animals and their settings. This section included nineteen participants. After implementing image media the learning motivation scores of participants significantly increased as confirmed by a paired sample t-test (p < 0.05; Cohen’s d = 4.73) indicating a very large effect size. The qualitative results demonstrated that participants showed higher levels of emotional engagement along with verbal communication and they continued tasks while working with peers based on classroom observations. The research shows that image-based media help both increase motivation levels and encourage valuable cognitive and social engagement during early childhood education. This study demonstrates how culturally relevant visual content available at low cost can build highly engaging learning places that respect child development in underfunded early education facilities. The paper presents implications for early childhood motivation research together with recommendations for educational implementation.